Islamic Branding - Mohammed Abdullah, Abdulhameed Mohammed; Mustafa, Siti Aisyah; Harun, Amran (Penerbit UTHM, 2020)
The market of halal food and Islamic finance sector which have increased dramatically in the past decade and many other Islamic products and services including cosmetics, real estate, hotels, fashion and insurance, (Alserhan, 2010a), have amplified the role of Islamic brand at present. Fatema et al. (2013) stated that Islamic marketing is aimed at Muslim consumers who are significantly different from the average consumer and that it utilizes specific recourses, skills, and tools that are directly relating and attractive to this particular segment. Therefore, with the presence of Muslim customers, this market segment can be targeted, reached and to a certain extent, predicted by marketers. The demographic changes and purchasing power of Muslim consumers and the success of Muslim businessmen have begun to make Islamic marketing an intellectually and managerially attractive area. As a result, the use of Islamic brands as marketing strategies has intensified in academic circles within the past few years, both inside and outside the Islamic world (Alserhan, 2010). This claim was further supported by Wilson and Liu (2011), stating that the phenomenon of Islamic branding as a new and independent discipline has attracted the attention of both academics and practitioners.